A "one-for-three" strategy through a facile one-step hydrothermal engineering of commercial MoO3 for high-performance proton storage. Issue 8 (2nd February 2022) - Liu, Weifeng; Zhang, Zhi; Shi, Junjie; Zheng, Yifan; Wu, Yonghui; Fu, Xiutao; Liu, Nishuang; Su, Jun; Gao, Yihua
Abstract : A "one-for-three" strategy is proposed to regulate commercial MoO3 nanopowders through a simple one-step hydrothermal process. The modified MoO3 nanobelt electrode shows much improved electrochemical performance in proton storage. Abstract : The sluggish diffusion kinetics of metal ions and irreversible structural transition of electrode materials lead to serious decay of electrochemical performance. In this work, a "one-for-three" strategy is demonstrated to engineer commercial MoO3 nanopowders by adjusting the morphology, coating a thin layer of conductive PANI and introducing oxygen vacancy through a simple one-step hydrothermal process. Benefiting from the synergistic effects of enhanced charge transfer kinetics, improved conductivity and robust structural stability, the optimized MoO3 nanobelts show excellent performance in proton storage. The MoO3 electrode delivers a record-high performance of 1307.4 F g −1 (236.1 mA h g −1 ) at 1.0 A g −1, excellent rate capability with a capacitance retention of 55.3% at 50.0 A g −1, and stable cycling performance with a capacitance retention of 95.5% after 6000 cycles. Furthermore, the redox reaction mechanism of the MoO3 electrode in proton battery has been revealed. The fabricated P100-MoO3 //NAC proton storage hybrid device shows a maximum energy density of 43.3 W h kg −1 at 800 W kg −1 and noteworthy cycling stability. This novel design sheds light on the improved electrochemical kinetics in the energy storage of MoO3 -based electrodes with different electrolytes.